Qualidade de água superficial em bacia hidrográfica com exploração mista leite/grãos - Busnello, Fábio José (2012)
The impact of dairy farming on water is still little known. The purpose of this study was to assess the impact of dairy farming on the quality of surface waters in regard to transfer of pollutants from the soil to the water in a water catchment basin (BH). Water samples from six locations were collected in the BH of Vila Maria, RS, on six dates from the month of January to July 2011 with an adapted type BH-48 sampling device. Collection locations were: spring in the midst of native forest (T1a-control); point downstream from the thalweg (T1b), affected by dairy farming; spring in the midst of a cropped area (T2a), and at a point downstream from the thalweg affected by dairy farming and the cropped area (T2b); at a point of the secondary thalweg (T3) affected by uses T1a, T1b, T2a and T2b; and at the mouth of the BH (Ex). The following were analyzed in the water samples: pH, turbidity, color, hardness, conductivity, dissolved oxygen, nitrogen in the form of (N-NH4+) and (N-NO3-), total phosphorus (PT) and soluble phosphorus (PS), potassium (K+) and sodium (Na+), iron (Fe3+), zinc (Zn+), copper (Cu+), and sediment concentration. The results were compared with those recommended by CONAMA, and analyzed by ANOVA (completely randomized design in split plots in time), and the Tukey test was applied when appropriate. The land use in the watershed affects water quality. Water parameters, such as N-NH4+, PT, PS and turbidity are negatively altered in at least one occasion during the monitoring. However, 4 OD and N-NO3 - levels were compatible with water quality standards for Class II